PREPARATION OF VACCINE FOR DIABETIC FOOT PATHOGENIC BACTERIA USING LOW LEVEL DIODE LASER - Zainab Awad Radi (Basrah Journal of Veterinary Research)
Since the invention of laser in 1960, lasers have been developed and approved in many fields. Lasers can now be regarded as practical tools with unique properties that have been utilized effectively in several applications in fields of medical and biological sciences. six bacterial isolates were isolated from human samples of diabetic foot infections, which used for preparation of vaccines. The experiment was conducted on fifteen adult male rabbits, they were divided into three groups with 5 rabbits each. After irradiation of the bacterial suspensions with the diode laser for different exposure times and different frequencies, and the wavelengths used were (660, 820, 915 ) nm, the growth of bacterial isolates decreased until killed of bacteria at ( 40) min. The aim of the current study was to preparation of vaccines (live attenuated and killed) by irradiation of the bacteria by the low level diode laser. Wavelength (660) nm was more effective in killing the bacteria, and the variations were not significant between the live attenuated and the killed vaccine